Computational study on the structural and optoelectronic properties of a carbazole-benzothiadiazole based conjugated oligomer with various alkyl side-chain lengths - Franco, Francisco C., Jr. (Animo Repository, 2017)
The effect of the alkyl side-chain length on the structural and optoelectronic properties of poly[N-9′-heptadecanyl-27-carbazole-alt-55-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT) conjugated oligomers have been studied by density functional theory (DFT) and time-dependent density functional theory (TD-DFT). The study was carried out by varying the length of alkyl side-chain attached to the nitrogen atom of the carbazole unit of the PCDTBT oligomers. The structural properties of the optimised oligomers were then studied by determining the bond-length alternation and dihedral angles (Φ) for various side-chain lengths. Total energy calculations for the determination of HOMO energy (EHOMO), LUMO energy (ELUMO), and fundamental energy gap (EGap) were performed using DFT at the B3LYP/6-31G(d), while the first singlet excitation energies (EOpt) were calculated by TD-DFT also at the same level of theory. It was observed that there are no significant structural changes occurring as the alkyl chain lengths are varied. For the electronic properties, very small differences (i.e. ~0.01 eV) were observed for EGap and EOpt while the exciton binding energies (EB) were virtually the same. The results suggest that using shorter alkyl side-chains do not significantly affect the structural and optoelectronic properties of the carbazole-benzothiadiazole based polymer. The observations can aid future computational design studies of analogous systems by reducing large structures thus decreasing computational costs. © 2016 Informa UK Limited, trading as Taylor & Francis Group.